Treasures from an unknown reign: Shunzhi porcelain, 1644-1661 - Butler, Michael, 1927-2013; Curtis, Julia B.; Little, Stephen, 1954-; Honolulu Academy of Arts.; Trammel & Margaret Crow Collection of Asian Art. (Alexandria, Va. : Art Services International, 2002)
The Shunzhi era (1644-61), marking the end of the Ming Dynasty and the beginning of the Qing, was a transitional period in Chinese history. By the late 1630s, painters on porcelain had developed a new, highly recognizable, and successful style. In the Shunzhi era, there was a strong emphasis on individual works of art, each one unique.
Catalog of an exhibition held at Honolulu Academy of Arts, Honolulu, Trammel & Margaret Crow Collection of Asian Art, Dallas, and University of Virginia Art Museum, Charlottesville.
Keywords: z; Porcelain, Chinese -- Ming-Qing dynasties, -- Exhibitions. -- 1368-1912; Porcelain, Chinese -- Ming-Qing dynasties